Prognostic Significance of Cyclic Seizures in Status Epilepticus. Issue 6 (November 2021) - Zorlu, Musab M.; Chuang, David T.; Buyukozkan, Mustafa; Aydemir, Seyhmus; Zarnegar, Reza
Abstract : Purpose: Status epilepticus (SE) is a commonly encountered neurologic condition associated with high mortality rates. Cyclic seizures (CS) are a common form of SE, but its prognostic significance has not been well established. In this retrospective study, the mortality of cyclic versus noncyclic forms (NCSs) of SE are compared. Methods: A total of 271 patients were identified as having seizures or SE on EEG reports, of which 65 patients were confirmed as having SE. Based on EEG characteristics, the patients were then classified as cyclic or noncyclic patterns. Cyclic seizures were defined as recurrent seizures occurring at nearly regular and uniform intervals. Noncyclic form included all other patterns of SE. Pertinent clinical data were collected and reviewed for each case. Results: Of the 65 patients with SE, 25 patients had CS and 40 patients had NCS. Patients with CS showed a lower rate of in-hospital mortality although not statistically significant ( P = 0.19). When looking at patients younger than 75 years, the CS group had significantly lower in-hospital mortality rate ( P = 0.007). Conclusions: The findings of this study suggest that CS may have a more favorable outcome compared with NCS in patients younger than 75 years. This study is also the first to report the rate of CS among all cases of confirmed SE (38%). Future studies with a larger sample size are needed to further evaluate the difference in outcome between CS and NCS. Abstract : Supplemental Digital Content is Available in the Text.